Efficient Synthesis of Phosphonamidates through One‐Pot Sequential Reactions of Phosphonites with Iodine and Amines. Issue 63 (2nd October 2020) - Chen, Xunwei; Luo, Wenjun; Wang, Yanlin; Li, Zikang; Ma, Xiaorui; Peng, Ai‐Yun
Abstract: A one‐pot sequential strategy to construct phosphonamidates has been developed by generating phosphonites in situ from arylmagnesium bromides and triethyl phosphite followed by treatment with iodine and amines. A variety of phosphonamidates were obtained with good to excellent yields at room temperature from easily available materials. Abstract : Phosphonamidates in one pot : An iodine‐mediated one‐pot sequential phosphonoamidation of phosphonites with amines is developed. A variety of phosphonamidates were obtained from easily available starting materials with good to excellent yields under mild conditions.